THE FLOW OF INTERACTION THROUGH ONLINE DISCUSSION IN THE ENGLISH LANGUAGE CLASSROOM - Wina, Florentina Iriyanti; Salam, Urai; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research entitled The Flow of Interaction through Online Discussion in the English Language Classroom.Specifically, the aim of this research is find out the flow of interaction within online discussion in fourth semester learner of English Study Program. The method was Case Study. The data was collected through printing all posting from Yahoogroupsbecause the discussion and information exchange took place in that online group discussion. Firstly, this research produced how all learners respond to instructor’s posting. It can be from the instructor to the learner, the learner to the instructor and learner to the other learner with an expanding posting. Secondly, the writer categorized the learners’ postings into four categories represented their responses toward the topics given in the online discussion forum. From four episodes that were analyzed, the learners’ responses were distinguished into five categories, they are: social function, asking question/clarification, answering question, agreement/disagreement, and emerging ideas.The result of the data analysis have been significantly provides useful evidence on the instructor’s communication, the online interaction and the learners responses categories. Learners have expressed their satisfaction with online learning and with collaborative work. The flow of interaction among instructor and learners were more intensive toward teaching learning with ICT. Keywords : ICT, Online Discussion, The Flow of Interaction Abstrak: Penelitian ini berjudul The Flow of Interaction through Online Discussion in the English Language Classroom. Tujuan dari penelitian ini adalah untuk mengetahui arah interaksi dalam diskusi online pada mahasiswa semester empat program studi Bahasa Inggris. Metode yang digunakan adalah Case Study. Karena proses diskusi dan sumber informasinya sudah terekam dalam Yahoogroups maka proses analisis diambil melalui Yahoogroups. Pertama, penelitian ini membuktikan bagaimana semua mahasiswa merespon postingan instruktur. Postingan tersebut bias saja postingan yang berasal dari instruktur ke mahasiswa, mahasiswa ke instruktur atau pun seorang mahasiswa dengan postingan yang ditujukan untuk banyak mahasiswa. Kedua, penulis membuat postingan menjadi lima kategori dari empat episode berdasarkan diskusi online. Kelima kategori itu diantaranya, social function, asking question/clarification, answering question, agreement/disagreement, and emerging ideas. Hasil dari penelitian ini memberikan fakta yang signifikan bahwa mahasiswa merasa puas dengan belajar secara online. Kata kunci: ICT, Online Discussion, The Flow of Interaction